Նշխարներ «Նոր Մարութայի» աւետարանի մեկնութեան հայերէն թարգմանութիւնից - Քէօսէեան, Յակոբ (Մայր Աթոռոյ Սրբոյ Էջմիածնի)
В средневековой сирийской литературе известны два автора под именем «Марута». Первый из них — автор агиографического сборника «Восточные мученики» Марута Майферкатский (†420 г.), второй — книжник VI—VII веков патриарх города Тагрита (640—649), который известен своими антихалхедонскими взглядами. Поэтому весьма закономерен интерес армянских церковных книжников к его наследию. В статье впервые публикуются армянские переводы отрывков толкования Евангелия Маруты Тагритского.In the medieval Syriac literature, two authors are known under the name of “Maruta”. The first one is Maruta of Mayferkat (†420), the author of the hagiographic collection entitled Eastern Martyrs. The second scholar of the 6th—7th centuries was the patriarch of the city of Tagrit (640—649) known for his anti- Chalcedonian views. Therefore, the interest of the Armenian Church scholars in his written heritage is quite natural. In this article, Armenian translations of excerpts from the Commentary on the Gospel of Maruta of Tagrit are published for the first time.
Keywords: Christianity; Literature